Well-designed Te/SnS2/Ag artificial nanoleaves for enabling and enhancing visible-light driven overall splitting of pure water. (September 2017) - Yan, Changzeng; Xue, Xiaolan; Zhang, Wenjun; Li, Xiaojie; Liu, Juan; Yang, Songyuan; Hu, Yi; Chen, Renpeng; Yan, Yaping; Zhu, Guoyin; Kang, Zhenhui; Kang, Dae Joon; et al.
Abstract: To produce hydrogen and oxygen from photocatalytic overall splitting of pure water provides a promising green route to directly convert solar energy to clean fuel. However, the design and fabrication of high-efficiency photocatalyst is challenging. Here we present that by connecting different nanostructures together in a rational fashion, components that cannot individually split water into H2 and O2 can work together as efficient photocatalyst with high solar-to-hydrogen (STH) energy conversion efficiency and avoid the use of any sacrificial reagent. Specifically, Te/SnS2 /Ag artificial nanoleaves (ANLs) consist of ultrathin SnS2 nanoplates grown on Te nanowires and decorated with numerous Ag nanoparticles. The appropriate band structure of Te/SnS2 p-n junctions and the surface plasmon resonance of Ag nanoparticles synergistically enhance the quantum yield and separation efficiency of electron-hole pairs. As a result, Te/SnS2 /Ag ANLs enable visible-light driven overall water-splitting without any sacrificial reagent and exhibit high H2 and O2 production rates of 332.4 and 166.2 μmol h −1, respectively. Well-preserved structure after long-term measurement indicates its high stability. It represents a feasible approach for direct H2 production from only sunlight, pure water, and rationally-designed ANL photocatalysts. Graphical abstract: Highlights: Te/SnS2 /Ag ANLs heterostructure is prepared to catalyze overall water splitting. The catalyst show impressive H2 and O2 production rate under visible light. The structure and efficiency of catalyst shows no degradation after 10 days.